P202 Risk Factors For Early Mortality After Lung Cancer Resection: A Study of the UK National Lung Cancer Audit. (19th November 2012) - Powell, HA; Tata, LJ; Baldwin, DR; Khakwani, A; Stanley, R; Hubbard, RB
Abstract : Introduction: Surgical resection is the best chance of cure for most patients with non-small cell lung cancer (NSCLC), for whom 5-year survival is otherwise poor. Selection of patients for surgery should include an estimation of the likely post-operative mortality risk but the tool often used in UK practise is a predictive score that was developed using a French database of thoracic surgical procedures, not specific to lung cancer. Methods: We used data from the National Lung Cancer Audit linked with Hospital Episode Statistics to estimate the influence of pre-operative patient and tumour factors, and the type of procedure on the odds of death at 30 and 90 days after potentially curative surgery for NSCLC. We used logistic regression to determine which factors were associated with early post-operative mortality and then calculated the percentage of patients who died within 90 days of surgery, stratified by the strongest predictors of early post-operative mortality. Results: We identified 12, 096 patients who had potentially curative surgery for NSCLC in England between January 2004 and March 2010. Three per cent (n=387) and 6% (n=792) of patients died within 30 and 90 days respectively. Of the 12 clinical and socio-demographic factors assessed, age and type of procedure were consistently the most important predictors of early post-operative mortality: Odds ratio (OR) for death at 30 days for pneumonectomy compared with lobectomy 3.03, 95% confidence interval (CI) 2.32–3.94; and for each year increase in age OR 1.06, 95% CI 1.04–1.07. Performance status, co-morbidity score and sex and were also significantly associated with the outcomes. Table 1 shows the percentage of patients who died within 90 days of either lobectomy or pneumonectomy, stratified by age and performance status. Conclusion: The estimation of post-operative mortality risk is a crucial part of management of patients with NSCLC. Overall mortality following surgery for NSCLC in England is currently 3% at 30-days and 6% at 90-days. We present UK data, stratified by age and performance status, which could be used in clinical practise to assist with the estimation of early post-operative mortality risk.